Cobertura permanente de solo com leguminosas herbáceas perenes no cultivo de bananeiras no médio Vale do Jequitinhonha - Quaresma, Mateus Augusto Lima (2014)
The region of the caatinga is characterized by high temperatures during the year and low rainfall. These regional climate factors demand the adoption of practices that increase the efficiency and sustainability of local farming. Thus, we aimed to evaluate